Maslahah and Gender Perspectives on Granting Polygamy Permits: Study of the Enrekang Religious Court Decision Number 28/Pdt.G/2021/PA.Ek - Muhyiddin Muhyiddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
The provisions for granting polygamy permits include facultative and cumulative requirements. The application in Case Number 28/Pdt.G/2021/PA.Ek needs to meet the facultative requirements. However, in their decision, the panel of judges granted the quo request. Research is required to dissect the significance of the arguments used by the Petitioner and the considerations used by the judge by placing them in the spectrum of Islamic thought regarding polygamy to find their relevance to granting permits. The approach used in this research is socio-legal. In this case, the ma?la?a? perspective in Islamic law and gender in social sciences will be used as theoretical tools to dissect the research object. Based on the theory of ma?la?a?, it is understood that the considerations in the quo case do not represent the meaning and concept of ma?la?a? and instead tend to illustrate the mafsada in the choice of legal basis used. Meanwhile, considering benefits in the quo decision is used to legitimize polygamy. From the gender analysis, it is understood that the considerations used by the panel of judges reflect the logic of oppression against women and legitimize the site of pressure through the ma?la?a? argument. The choice of legal basis by the Panel of Judges in the quo case reflects the situation of oppression where natural resources are domesticated and controlled as a reproduction machine.